THE CRYSTAL CHEMISTRY OF SCHERBAKOVITE FROM THE KHIBINA MASSIF, KOLA PENINSULA, RUSSIA - Uvarova Y.A.; Sokolova E.; Hawthorne F.C.; Liferovich R.P.; Mitchell R.H. (My University, 2003)
The crystal structure of shcherbakovite from Mount Rasvumchorr, Khibina massif, Kola Peninsula, Russia, ideally K2 Na Ti 4+ 2 O (OH) (Si4O12), a 8.1538(4), b 10.5569(5), c 13.9882(6) A, V 1204.1(2) A 3 , space group Imma, Z = 4, Dcalc 3.194 g/cm 3 , has been refined to R1 = 3.2% for 960 unique (Fo > 4σF) reflections collected on a Bruker single-crystal P4 diffractometer equipped with a CCD detector and MoKX-radiation. Shcherbakovite occurs in late (hydrothermal) shallowly dipping veins of natrolite and is associated with natrolite, aegirine, K-feldspar, strontian apatite, titanite, spherulitic baryllite and rare pyrrhotite and chalcopyrite. Electron-microprobe analysis gave SiO2 40.57, TiO2 18.87, Fe2O3 1.05, MnO 0.06, BaO 6.7, CaO 0.20, K2O 13.22, Na2O 5.59, Nb2O5 10.49, SrO 0.08, ZrO2 0.84, Ta2O5 0.06, (H2O)calc 0.73, sum 97.83 wt.%. The amount of H2O was determined from crystal-structure analysis. There is one tetrahedrally coordinated T site, 1.607 A, occupied by Si. There are two octahedrally coordinated sites, M(1), occupied by (Ti0.68 Nb0.32 1.00), with = 2.016 A, and M(2), occupied by (Ti0.72 Nb0.15 Fe 3+ 0.08 Zr0.04 1.01), with = 1.999 A. The M(1) and M(2) sites are separated by 0.477 A, and hence cannot be occupied simultaneously at a local level. There are three interstitial A sites: the A(1) site is (9)-coordinated and is occupied by (K0.66 Ba0.23 Na0.07 Ca0.02), with = 2.952 A; the A(2) site is (8)-coordinated and is occupied by K, with = 2.861 A, and the A(3) site is (6)-coordinated and is occupied by Na, with = 2.493 A. Shcherbakovite is a K-analogue of batisite, ideally Ba Na2 Ti 4+ 2 O2 (Si4O12). Shcherbakovite is related to batisite by substitution of K for Ba and K for Na. "Noonkanbahite", ideally Ba K Na Ti 4+ 2 O2 (Si4O12), has never been approved by the IMA as a new mineral species. Based on the crystal chemistry of this structure type, the general formula of these minerals may be written as A B C M2 2 (Si4O12), with the following end-member compositions: batisite A = Ba, B = Na, C = Na; shcherbakovite, A = K, B = K, C = Na; "noonkanbahite", A = Ba, B = K, C = Na; unnamed, A = K, B = Na, C = Na.
Keywords: shcherbakovite; batisite; end-member; crystal-structure refinement